A Socio-demographic Study of Destination Management for Coastal Tourism in Phuket - WONGWATTANAKIT, Chatchawan; LOHATEPANONT, Manoj; PORNCHAIWISESKUL, Pongsa (Journal of Environmental Management and Tourism, 2017)
This study examined the effects of socio-demographic variables on destination satisfaction with beaches in Phuket, Thailand, a renowned Sea-Sand-Sun destination. Phuket has consistently been top ranked for coastal tourism, with 12.5 million tourists generating USD 9.04 million (34.62 THB = 1 USD as of April 30, 2017) revenue in 2015. In order to study the relationship between demographic variables and satisfaction, a survey was given to 1,221 visitors in the departure hall of Phuket International Airport. Analysis of Variance (ANOVA) was employed to examine the interaction between tourist socio-demographics and tourist satisfaction. The findings showed nationality had the most significant influence on the overall tourist satisfaction with Maikhao beach, Surin-Bangtao beach, and Kata-Karon beach. Education was a significant factor concerning Patong-Kamala beach, and income was directly correlated with tourist satisfaction in the case of Kata-Karon beach. Additional analysis showed that being a first time visitor or repeat visitor, and number of nights spent had significant effects on tourist satisfaction. The findings reveal considerable differences in satisfaction levels between tourists’ profiles and destinations that will be essential in helping tourism decision makers, local government and businesses to comprehensively manage and market to specific tourist segments.